Antibacterial activity of Cathormion umbellatum (Bangladesh Journal of Pharmacology, 2021)
The aim of this study was to determine the antibacterial activity of Cathormion umbellatum extracts against seven antibiotic-resistant bacteria. The pods, leaves and branches of C. umbellatum were extracted with ethanol and methanol. The disc diffusion assay was used to screen the antibacterial activity and broth microdilution and colorimetric assay were used to measure the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. The result indicated that the highest inhibition zone (11 mm) was presented in ethanolic pods extract against multidrug resistance Klebsiella pneumoniae. The lowest MIC value of 0.05 mg/mL was obtained from branch extracted with ethanol against colistin resistant Pseudomonas aeruginosa. The lowest MBC values of 1.56 mg/mL were obtained when using C. umbellatum leaves extracted with methanol against all test antibiotic-resistant bacteria. This is the first report presented C. umbellatum extracts have the potential to eliminate antibiotic-resistant bacteria in patients. These findings show the antibacterial effect of C. umbellatum.